Canadian Geoscience: Charting New Territory in the 21st Century: The Geological Association of Canada Presidential Address, GeoCanada 2010, May 10, 2010 - Lebel, Daniel (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2010)
SUMMARY The Geological Association of Canada Presidential Address is traditionally delivered by the outgoing President of the Association at the annual general meeting; in this case, GeoCanada 2010, held in Calgary, Alberta, provided the opportunity for the 2010 address. The objectives of the address, and of this paper, are: To outline the status and trend information and observations on what economic and natural drivers influenced geoscience societies and geoscience careers in Canada over the last 10 years; To anticipate what the future might hold for individual geoscientists and the organizations for whom they work; To encourage more support for geoscience societies from geoscientists and their employers; and To call for a renewal of cooperation between geoscience associations in Canada and abroad.